Dinámica de la inflación en México: Un análisis de wavelets - Josué Fernando Cortés Espada; Daniel Sámano; Rubí T. Gutiérrez Villanueva (Banco de México, 2019)
– This paper uses the wavelet methodology to analyze the dynamics of inflation in Mexico at different frequencies over time. First, we analyze the monthly behavior of the headline, core, and noncore inflation from January 2007 to December 2018. Subsequently, the decomposition shows that the shocks on headline inflation in 2017 were mainly associated with the high-frequency component and they did not generate changes in its low-frequency component.
Keywords: C19; C49; C65; E31; 330; Inflation; Wavelet decomposition; Wavelet variance; Trend inflation